Bilingual writing coactivation: Lexical and sublexical processing in a word dictation task. Issue 5 (14th November 2021) - Iniesta, Antonio; Paolieri, Daniela; Serrano, Francisca; Bajo, M. Teresa
Abstract: Bilinguals' two languages seem to be coactivated in parallel during reading, speaking, and listening. However, this coactivation in writing has been scarcely studied. This study aimed to assess orthographic coactivation during spelling-to-dictation. We took advantage of the presence of polyvalent graphemes in Spanish (one phonological representation with two orthographic specifications, e.g., / b /for both the graphemes v and b) to manipulate orthographic congruency. Spanish–English bilinguals were presented with cross-linguistic congruent (mov ement–mov imiento) and incongruent words (gov ernment–gob ierno) for a dictation task. The time and accuracy to initiate writing and to type the rest-of-word (lexical and sublexical processing) were recorded in both the native language (L1) and the second language (L2). Results revealed no differences between conditions in monolinguals. Bilinguals showed a congruency and language interaction with better performance for congruent stimuli, which was evident from the beginning of typing in L2. Language coactivation and lexical–sublexical interaction during bilinguals' writing are discussed.